1993
DOI: 10.1093/nar/21.10.2415
|View full text |Cite
|
Sign up to set email alerts
|

Variation andin vitrosplicing of group I introns in rRNA genes ofPneumocystis carinii

Abstract: The sequences of the rRNA genes of Pneumocystis carinii from rat and human sources demonstrate three distinct genotypes based on the group I introns present in these genes. One rat isolate (Pc1) contains such introns in its 16S and 26S rRNA genes, while another rat isolate (Pc2) and a human isolate (Pc3) only contain an intron in the 26S rRNA gene. The four introns all catalyze their own excision from RNA transcripts, and this reaction is inhibited by the anti-pneumocystis drug pentamidine and its analogues. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 34 publications
(77 reference statements)
5
86
0
1
Order By: Relevance
“…hominis has only one copy of the rRNA gene (22), our sequence analysis indicated the presence of two different bases at one position in strains from 36 (60%) specimens and provides evidence in support of infection with more than one type of P. carinii (14). An incidence of 33% mixed infections has previously been reported for AIDS patients (23) and from analysis of the mt LSU rRNA and ITS loci (10,11,14). In this study, we found mixed infections in 60% of the specimens that we analyzed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…hominis has only one copy of the rRNA gene (22), our sequence analysis indicated the presence of two different bases at one position in strains from 36 (60%) specimens and provides evidence in support of infection with more than one type of P. carinii (14). An incidence of 33% mixed infections has previously been reported for AIDS patients (23) and from analysis of the mt LSU rRNA and ITS loci (10,11,14). In this study, we found mixed infections in 60% of the specimens that we analyzed.…”
Section: Discussionmentioning
confidence: 64%
“…The 5S rRNA gene also has limited sequence variation, with polymorphisms reported at five positions. Analysis of the sequence of a portion of the nuclear rRNA operon of the organism from BAL samples from five HIV-infected patients in the United States failed to show any differences (14). It is also possible, however, that the polymorphism could be explained in part by the presence of heterozygosity in diploid-stage organisms in the sample.…”
Section: Discussionmentioning
confidence: 91%
“…To date, the mtLSU rRNA sequence has been reported from P. carinii organisms infecting nine different mammalian species: human, rat (two divergent sequence types), mouse, rabbit, pig, horse, shrew, ferret (five divergent sequence types), and rhesus macaque (17,23,37,46). The genetic diversity of P. carinii was examined at other loci such as the mitochondrial small subunit of rRNA (28), the nuclear ribosomal RNA operon (32,46), ␣-and ␤-tubulin (18,43), arom (5), thymidilate synthetase (30,35), DHPS (31), and more recently manganese-dependent superoxide dismutase (16). However, only a small variety of mammalian hosts with P. carinii were examined in former analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The NJ tree (Fig. 3) reflects a close relationship between GP-D and the P. carinii group I introns (Liu and Leibowitz, 1993). So it should not be interpreted, however, that all introns occurring at a particular site are necessarily closely related or that introns at different sites in the same organisms cannot be homologous (Hibbett, 1996).…”
mentioning
confidence: 99%